دور السياسة النقدية في ضبط المعروض النقدي في الجزائر للفترة 2001-2021 - بن سالم, فطحيزة عمارة; عدنان, عبيد; معتز بالله, كرشو (جامعة الوادي - University of Eloued, 2023)
إن البنك المركزي له أهمية كبيرة في الدولة من حيث توليه مهمة الإصدار النقدي ,ومهمة إدارة السياسة النقدية لكونه يتمتع بسلطة رقابية على البنوك ,ونهدف من خلال هذه الدراسة إلى معرفة الدور الذي تلعبه السلطة النقدية في ضبط العرض النقدي في الجزائر (2001 – 2021) ,وتوصلنا الى أن السلطة النقدية الممثلة في البنك المركزي تلعب دور المحرك الرئيسي للنشاط الإقتصادي من خلال تحكمها في العرض النقدي باستخدام أدوات ووسائل السياسة النقدية التي تهدف بطريقة مباشرة أو غير مباشرة الى ضبط عرض النقود بما يتماشى والنشاط الاقتصادي ,وكذا تحقيق الاهداف الاقتصادية المنشودة .وقد تم إسقاط هذه الجوانب على الاقتصاد الجزائري وخلصنا الى أن بنك الجزائر ركز بشكل كبير على إستخدام أداة الإحتياطي الإجباري إلى جانب أداة تسهيلات الودائع المغلة للفائدة ,وكذا أداة إسترجاع السيولة للتحكم بشكل فعلي في إمتصاص فائض السيولة ,كما تميز عرض النقود في الجزائر خلال فترة الدراسة بالنمو المتزايد والمستمر في معدلاته مع إرتباط هذا النمو والتغيير في مقابلات الكتلة النقدية وبالأخص مقابل الموجودات الخارجية التي إحتلت الصدارة في إنشاء النقود في الجزائر. The Central Bank has great importance in the state in terms of assuming the task of issuing money, and the task of managing monetary policy because it has supervisory authority over banks, and we aim through this study to know the role played by the monetary authority in controlling the money supply in Algeria (2001-2021), and we f ound that the monetary authority represented by the Central Bank plays the role of the main engine of economic activity through its control of the money supply using monetary policy tools and means that aim directly or These aspects have been projected on the Algerian economy and we concluded that the Bank of Algeria focused heavily on the use of the compulsory reserve instrument along with the interest-bearing deposit facility instrument, as well as the liquidity recovery tool to effectively control the absorption of excess liquidity, and the money supply in Algeria during the study period was characterized by increasing and continuous growth in its rates with the correlation of this growth and The change in the corresponding monetary mass, especially against external assets, which occupied the forefront in the creation of money in Algeria
Keywords: السلطة النقدية ,عرض النقود في الجزائر , السياسة النقدية , مقابلات الكتلة النقدي; Monetary Authority , Money Supply in Algeria , Monetary Policy , Monetary Mass Interviews